Niger : Investing for Prosperity - A Poverty Assessment - World Bank (Washington, DC, 2013)
This report examines poverty trends and distribution of the poor in this larger context, paying particular attention to the most recent past. The report contributes to our understanding of the progress made in combating poverty in three ways. First, it updates our knowledge of poverty outcomes by examining the trends in poverty and vulnerability, as well as the profile and distribution of the poor and vulnerable across the country. Second it looks at the most common shocks, and their scale and influence on the welfare of the population. Third, it highlights the progress the country has made in improving opportunities for acquiring human capital and increasing incomes in rural areas. In this respect the report examines changes in access to education and health and improvements in productivity and income in small holder agriculture. It also explores the potential impact of public investments in agriculture. The report finds that, the biggest achievement in the last decade has been the substantive improvement in opportunities to acquire human capital.